2013
DOI: 10.3389/fnbeh.2013.00046
|View full text |Cite
|
Sign up to set email alerts
|

Synergies between optical and physical variables in intercepting parabolic targets

Abstract: Interception requires precise estimation of time-to-contact (TTC) information. A long-standing view posits that all relevant information for extracting TTC is available in the angular variables, which result from the projection of distal objects onto the retina. The different timing models rooted in this tradition have consequently relied on combining visual angle and its rate of expansion in different ways with tau being the most well-known solution for TTC. The generalization of these models to timing parabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(54 citation statements)
references
References 57 publications
0
54
0
Order By: Relevance
“…While again Gómez and López-Moliner (2013) propose a way of integrating air resistance into their model of parabolic target interception, a relatively accurate and precise gravity prior (as brought forward by authors such as Lacquaniti and Zago) seems contradictory with effectively observed acceleration values of under 9.81 m/s 2 . And in fact, Flavell (2014) suggests that the gravity prior may actually not be set at 1g exactly, but rather at a value between 1g and just below 1g.…”
Section: Attunement To Earth Gravity: Interception Performance Under mentioning
confidence: 99%
“…While again Gómez and López-Moliner (2013) propose a way of integrating air resistance into their model of parabolic target interception, a relatively accurate and precise gravity prior (as brought forward by authors such as Lacquaniti and Zago) seems contradictory with effectively observed acceleration values of under 9.81 m/s 2 . And in fact, Flavell (2014) suggests that the gravity prior may actually not be set at 1g exactly, but rather at a value between 1g and just below 1g.…”
Section: Attunement To Earth Gravity: Interception Performance Under mentioning
confidence: 99%
“…Sometimes specific knowledge of fixed parameters or constants, such as Earth's gravitational acceleration or a ball's diameter or elasticity, is also referred to as an internal model. We will reserve the term “internal model” for an inner surrogate that mimics an external physical process; constants do not meet this standard, although they can act as constraints on the calibration of optical variables or visual-motor control laws (Gómez & López-Moliner, 2013; Jacobs & Michaels, 2006). Further, the fidelity of an internal model, as well as its temporal duration, are rarely specified.…”
Section: Introductionmentioning
confidence: 99%
“…The next step is an analysis on the subject level for the chosen cues. Then, we try out different combinations of and , which, according to a gravity-based TTC model ("GS model"; Gómez & López-Moliner, 2013), might be used as approximate heuristics to estimate gravity. Finally, we employ Generalized Linear Mixed Modelling (Moscatelli & Lacquaniti, 2012) to assess whether participants used homogeneous or rather idiosyncratic strategies, and finish with a short assessment of the role of purely temporal information.…”
Section: Discussionmentioning
confidence: 99%
“…While thus all information necessary for distance recovery is readily available to the subject, it has been observed that distance may be underestimated in virtual environments, especially when these are scarce (Loomis & Knapp, 2003;Messing & Durgin, 2005). While the visual angle itself can be estimated with accuracy (McKee & Welch, 1992), its rate of change over time is very noisy, with Weber fractions of 10 % and beyond (Gómez & López-Moliner, 2013;Regan & Hamstra, 1993). Nonetheless, as suggested by the important, though contested role of the visual angle and its rate of expansion (for the parameter τ) in the literature on TTC estimation for linearly approaching targets (Lee & Reddish, 1981), it may still deliver some information, e. g. about the physical horizontal velocity.…”
Section: Optic Flow Analysismentioning
confidence: 99%
See 1 more Smart Citation